Counterfactual thought experiments in world politics : logical, methodological, and psychological perspectives - Tetlock, Philip E. (Philip Eyrikson), 1954-; Belkin, Aaron, 1966- (Princeton paperbacks, 1996)
Political scientists often ask themselves what might have been if history had unfolded differently: if Stalin had been ousted as General Party Secretary or if the United States had not dropped the bomb on Japan. Although scholars sometimes scoff at applying hypothetical reasoning to world politics, the contributors to this volume--including James Fearon, Richard Lebow, Margaret Levi, Bruce Russett, and Barry Weingast--find such counterfactual conjectures not only useful, but necessary for drawing causal inferences from historical data. Given the importance of counterfactuals, it is perhaps surprising that we lack standards for evaluating them. To fill this gap, Philip Tetlock and Aaron Belkin propose a set of criteria for distinguishing plausible from implausible counterfactual conjectures across a wide range of applications. The contributors to this volume make use of these and other criteria to evaluate counterfactuals that emerge in diverse methodological contexts including comparative case studies, game theory, and statistical analysis. Taken together, these essays go a long way toward establishing a more nuanced and rigorous framework for assessing counterfactual arguments about world politics in particular and about the social sciences more broadly.